2019
DOI: 10.2147/ott.s218524
|View full text |Cite|
|
Sign up to set email alerts
|

<p>The Multifunction Of miR-218-5p-Cx43 Axis In Breast Cancer</p>

Abstract: Background: Gemcitabine is proven to be the first-line standard treatment of breast cancers. Yet, little is known involving gemcitabine resistance and remains largely to be elucidated. Materials and methods: We evaluated the expression of Cx43 in gemcitabine-resistant cells and parental cells by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analyses. Dual-luciferase reporter assay was applied to examine the epigenetic regulator of Cx43. The role of miR-218-5p-Cx43 axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…miR-218 via its role in Wnt/β-catenin signaling represents a hot spot molecule in cancer studies, as dysregulation of this miRNA is strongly associated with different cancers [ 211 , 212 , 213 , 214 , 215 , 216 ]. Except for the cancers, miR-218-5p plays an essential role in the HF and skin development again through Wnt/β-catenin signaling by targeting and inhibiting SFRP2—the antagonist of this signaling pathway [ 76 ].…”
Section: Mirna Involvement In Hair Growth Regulationmentioning
confidence: 99%
“…miR-218 via its role in Wnt/β-catenin signaling represents a hot spot molecule in cancer studies, as dysregulation of this miRNA is strongly associated with different cancers [ 211 , 212 , 213 , 214 , 215 , 216 ]. Except for the cancers, miR-218-5p plays an essential role in the HF and skin development again through Wnt/β-catenin signaling by targeting and inhibiting SFRP2—the antagonist of this signaling pathway [ 76 ].…”
Section: Mirna Involvement In Hair Growth Regulationmentioning
confidence: 99%
“…Considering that overexpression of GDPD5 partly reversed the inhibiting effect of MAGI2‐AS3 silencing on NPC cellular progression, we aimed to preliminarily identify whether there were alternate targets for MAGI2‐AS3 in NPC. We kept our focus on the MAGI2‐AS3/miR‐218‐5p axis; accordingly, we referred to previous research and identified 20 mRNAs reported as miR‐218‐5p targets, namely Cx43, 25 LASP1, 26 TXNDC5, 27 , SHMT1, 28 TRAF1, TRAF2, TRAF5, 29 HMGB2, 30 HMGB1, 31 SEC61A1, 32 DDX21, 33 CD44, 34 DPH1, 35 CDK6, CCND1, 36 PRKCE, 37 SOST, SFRP2, 38 EGFR, 39 and TFF1 40 . We then aimed to confirm the correlation of these genes with MAGI2‐AS3.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-218-5p is a highly conserved miRNA in mammals, which has been considered as a tumour suppressor by inhibiting cell proliferation, migration, growth, and metastasis of many cancers, including breast cancer, prostate cancer, and cervical cancer [ 29 , 30 , 31 ]. Additionally, many studies also found that miR-218-5p can regulate skin and hair development [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%